Analysis of the institutional consequences of the isolation of Russian sport at the international level in the period 2022–2025 - Safronov R.V.; Kolesov D.I.; Kasatkin B.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to analyze the institutional consequences of the international isolation of Russian sport in 2022-2025, including the scope of restrictions, conditions for the admission of neutral athletes, organizational measures to overcome isolation, and the development of directions for the strategic institutional development of the sports system. Methods and structure of the study. The methodological study is based on the principles of institutional analysis and a systematic approach. The following methods were used: content analysis (of normative acts and documents of the IOC, FIFA, FIG, and the Ministry of Sport of the Russian Federation); comparative historical analysis (by stages: 2022, 2023, 2024); expert evaluation of publications in the scientific and business press. Results and conclusions. International isolation was not only competitive in nature, but also political and organizational, including the suspension of membership of organizations, cancellation of tournament participation, postponement of events, and exclusion from rankings. The partial admission of individual athletes under AIN (Authorized Individual Neutral) status was a formal compromise, but in fact only cemented institutional isolation for the long term. Russia’s adaptation strategies included restarting the national calendar, launching alternative formats (BRICS Games, Friendship Games), restructuring the reserve and developing the domestic competitive environment. The author concludes that a model of autonomous sports management has emerged, accompanied by risks of losing international competitiveness, distorting competitive motivation and limiting access to global standards.